Social Determinant Factors of Elderly as an Input in Enhancing Primary Health Care in Indonesia - Sharon Gondodiputro; Henni Djuhaeni (Faculty of Medicine Universitas Padjadjaran, 2019)
Objective: To analyze the differences of social determinant factors among elderly according to gender, in urban and rural areas in Indonesia. Indonesia is one of the most populated countries in the world, faces an increased number of elderly. This situation leads to the increase of degenerative diseases and demands of caregivers as well. The identification of social determinant factors of elderly has an important role in enhancing primary health care.Methods: A comparative study was carried out in 33 provinces in Indonesia using secondary data from Statistics Indonesia 2013. The variables included in this study were percentage of elderly according to education, marital status, occupation, income and living arrangements, divided in gender, urban and rural areas. The normally distributed data were analyzed using unpaired T test and not normally distributed data were analyzed using Mann-Whitney test. Results: This study showed that there were differences in education, occupation and income between urban and rural areas. In urban area, most of the elderly worked in industry and trade and in rural area they worked in agricultural, indicated huge risks of occupational haxards. Most of them were poor, still married, lived with spouses and family of three generations.Conclusions: It can be concluded that there were differences of social determinant factors (education, occupation and income) in elderly who live in urban and rural areas that can contribute to the risks of disease in elderly and these situations must be considered as an input to enhance the primary health care.Keywords: Elderly, gender, rural, social determinants, urban